Position paper of the German Cardiac Society on cardiac computed tomography for periprocedural planning and performance of cardiac interventions: From the Committee for Clinical Cardiovascular Medicine DGK-Positionspapier zur Schnittbildgebung Teil I: Kardiale Computertomographie zur periprozeduralen Planung und Durchführung von kardialen Interventionen: Aus der Kommission für Klinische Kardiovaskuläre Medizin - Ochs, Marco; Breitbart, Philipp; Sultan, Arian; Hell, Michaela; Schulz-Menger, Jeanette; Lurz, Philipp; Tillmanns, Christoph; Tesche, Christian; Linke, Axel; Achenbach, Stephan; Thiele, Holger; Rudolph, Tanja K.; et al. (Die Kardiologie, 2025)
The significance of cardiac computed tomography (CT) for the diagnosis or exclusion of coronary artery disease (CAD) is firmly established in the recommendations of the guidelines in the sense of an extended risk stratification and treatment management. Technological advances are now paving the way for new applications beyond diagnostics in periprocedural planning and guidance of cardiac interventions. Coronary CT angiography enables the noninvasive, patient-specific selection of strategic approaches including lesion preparation. In structural interventions the exact three-dimensional analysis of dimensions, spatial resolution and three-dimensional relationships as well as the appropriate selection of implants are made possible. While cardiac CT is already indispensable for preprocedural planning in transcatheter aortic valve implantation (TAVI), the procedure is also increasingly being utilized in invasive cardiology for planning of other structural and coronary interventions as well as electrophysiological procedures. The aim of this position paper is to categorize the areas of application of cardiac CT as a supportive method for cardiac interventions and to define standards for its application and interpretation.
CRIS-Team Scopus Importer:2025-04-01
Keywords: Cardiac computed tomography; Chronic coronary syndrome; Coronary artery disease; Structural heart disease; Valvular diseases